2021
DOI: 10.1016/j.jctube.2021.100218
|View full text |Cite
|
Sign up to set email alerts
|

Mini-review: Silico-tuberculosis

Abstract: Silicosis continues to be a serious health issue in many countries and its elimination by 2030 (a target set by WHO and the International Labour Organization in 1995) is virtually impossible. The risk to develop pulmonary tuberculosis for silicosis patients is higher than for non-silicosis people, and there is also an increased risk of both pulmonary and extrapulmonary tuberculosis in individuals exposed to silica. HIV coinfection adds further to the risk, and in some countries, such as South Africa, miners li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
1
20
0
4
Order By: Relevance
“…17 It is noted that most of the cases are reported from lower-and lower-middle income countries, reason, no Most of the existing literature suggests that male sex and the age of 25-54 years are the greater risks of developing silicosis/silicotuberculosis. 10,13,14 The same is also observed in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…17 It is noted that most of the cases are reported from lower-and lower-middle income countries, reason, no Most of the existing literature suggests that male sex and the age of 25-54 years are the greater risks of developing silicosis/silicotuberculosis. 10,13,14 The same is also observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Of 54 patients, 38.9% (21) patients had an occupation of quarry working followed by 18.5% (10) patients that had occupation of bore well digging and tile working. About 11.1% (6) population had occupation of tooth powder factory working, 7.4% (4) patients had road laying, 3.7% (2) had glass factory working, and the least 1.85%…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because its respiratory manifestations and imaging findings can be easily confused with TB, an important differential to rule out among patients with silica exposure is active pulmonary TB. In fact, studies have suggested that silica exposure is a risk factor for the development of TB [ 16 , 17 , 18 ]. A meta-analysis conducted by Ehrlich et al (2021) illustrated an increased likelihood of developing TB among those with occupational exposure to silica dust (relative risk of 4.01, 95% confidence interval 2.88–5.58) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumoconiosis is the most frequently found disease among all occupational diseases [ 1 ]. Silicosis is one of the most common pneumoconioses [ 2 ]. Silicosis is a pulmonary fibrosis disease caused by inhalation, retention, and pulmonary reaction to silica crystals that contain silicon dioxide (SiO2) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%